Straits Settlements Blue Book (imports/exports) 1901-1902 vol. 40-41 (London : Public Record Office)
Mengandungi Blue Book for the year 1901-02;'Straits Settlements return of imports and exports for the year 1901';'Recapitulatory and comparative statement of the value of imports into and exports from the Colony and of the Straits Settlements for the year 1899 and 1900 and 1901'.